2019
DOI: 10.1016/j.jtumed.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Types of polymerisation units and their intensity output in private dental clinics of twin cities in eastern province, KSA; a pilot study

Abstract: Objectives Light-cured resin-based composites (RBCs) are the preferred option to restore teeth. Dental light-curing units (LCUs) should deliver adequate light energy to ensure good mechanical properties, dimensional stability, and biocompatibility of the RBC. The aim of this study was to determine the types of LCUs and their intensity output in private dental clinics. Methods A form was developed to record information related to the type of curing lights and their inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
5
0
5
Order By: Relevance
“…Results indicate that 18% of analyzed units presented an inadequate light intensity (< 400 mW*cm-2). Similar results were obtained by Eren D et al, where values below recommended intensity constituted 10, 7% [7], as well as Alquria T et al, with 13% [13]. However, Madhusudhana K et al, reported an increase of up to 44% of units with inadequate intensities [31].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Results indicate that 18% of analyzed units presented an inadequate light intensity (< 400 mW*cm-2). Similar results were obtained by Eren D et al, where values below recommended intensity constituted 10, 7% [7], as well as Alquria T et al, with 13% [13]. However, Madhusudhana K et al, reported an increase of up to 44% of units with inadequate intensities [31].…”
Section: Discussionsupporting
confidence: 82%
“…Light sources are available in four types: Halogen, Light Emission Diode (LED), Xenon Plasma Arc (PAC) and Laser [12]. Halogen and LED are the most used in private dental clinics [13,14]. Halogen lamps were introduced in the '70s [15] and were considered as standard units for several years [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their mean value was 862.3 mW/cm 2 [14]. Another study done in private clinics in cities Dammam and Khobar also found a higher mean intensity of LED light-curing units, which was 865.2 mW/cm 2 [15]. That difference in mean value could be due to higher maintenance in private clinics.…”
Section: Discussionmentioning
confidence: 88%
“…4 A recent study done by Alquria et al, 2019 also showed trends of LED over QTH in private dental clinics. 11 One possible reason for the low usage of LED light could be the outdated knowledge of practitioners in Karachi, as LED lights were introduced at the end of the '90s and many practitioners are still not aware of their superior properties over blue light. 12 The biggest advantage of using LED units is their easy maintenance.…”
Section: Discussionmentioning
confidence: 99%